Role of Chabacano Language in Shaping Cultural Identity Among Generation Z in Ternate, Cavite - Astorga, John Mark; Nurchotimah, Aulia Sholichah Iman (International Journal of Religion Education and Law, 2026)
Chabacano language is a cultural heritage of Ternate, Cavite. It is a creole language originated from Moluccas during the time of European colonization. This paper explores the role of Chabacano language in shaping cultural identity among Generation Z in Ternate. To answer this, the researcher utilized Descriptive design using semi-structured interview. The participants of this study were carefully selected using Purposive sampling with the following criteria: (1) the participant must be a native of Ternate, (2) the participant must be a Chabacano speaker, and (3) the participant must be a Generation Z student of Ternate. The data were gathered through Messenger and Gmail. For the data analysis, the researcher used Thematic Analysis and generated 5 major themes. The findings show that Generation Z in Ternate show great interest in preserving Chabacano language, they find this language a marker of their cultural identity. In addition, they also acknowledge the importance of Chabacano language in community gatherings such as family events, cultural and religious festivals. The researcher recommend that Millennials and Generation Z should receive regular Chabacano Language Preservation Program through seminars for them to preserve the language effectively. The researcher also recommends the utilization of Chabacano Research among local schools and college in Ternate.